Lack of aggression and apparent altruism towards intruders in a primitive termite - Cooney, Feargus (R Soc Open Sci, 2016)
In eusocial insects, the ability to discriminate nest-mates from non-nest-mates is widespread and ensures that altruistic actions are directed towards kin and agonistic actions are directed towards non-relatives. Most tests of nest-mate recognition have focused on hymenopterans, and suggest that cooperation typically evolves in tandem with strong antagonism towards non-nest-mates. Here, we present evidence from a phylogenetically and behaviourally basal termite species that workers discriminate members of foreign colonies. However, contrary to our expectations, foreign intruders were the recipients of more rather than less cooperative behaviour and were not subjected to elevated aggression. We suggest that relationships between groups may be much more peaceable in basal termites compared with eusocial hymenoptera, owing to energetic and temporal constraints on colony growth, and the reduced incentive that totipotent workers (who may inherit breeding status) have to contribute to self-sacrificial intergroup conflict.